Model of dynamic descriptions of the strapdown inertial system - Казак, В. М.; Лейва, Родриго Каналес; Яковицкая, Е. Ю. (Problems of Informatization and Control, 2008)
The ways of decrease in expenses for certified tests are analyzed. The mathematical model of inertial navigation system is offered